Effects of Mulch Type, Plant Cultivar, and Insecticide Use on Sweet Potato Whitefly Population in Chili Pepper - Andi Nasruddin; Nurariaty Agus; Alam Saubil; Jumardi Jumardi; Burhanuddin Rasyid; Andry Siriniang; Andi Dirham Nasruddin; Firdaus Firdaus; Ahwiyah Ekawaty Said (Scientifica)
One of the most devastating pests of chili pepper is the sweet potato whitefly (SPW), Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae). It sucks plant sap, emits honeydew on which sooty mold fungi grow, and transmits the pepper yellow leaf curl Indonesia virus (PepYLCIV), the most damaging viral disease of chili in Indonesia. Farmers rely mainly on insecticide to control the insect with two to three sprays in a week. To reduce the insecticide use, an integrated approach needs to be developed. Therefore, the current study evaluated the effectiveness of the integration of reflective mulch, host plant resistance, and insecticide use for managing the sweet potato whitefly on the chili pepper. In 2018, a complete randomized block design was used in three separate trials to assess the effects of mulch, cultivar, or insecticide application frequency on the numbers of whitefly eggs, nymphs, and adults. In 2019, a split-split plot design was used to evaluate the effects of the integration of mulch, cultivar, and insecticide application frequency on the numbers of whitefly eggs, nymphs, and adults. The results showed that the reflective silver mulch had significantly lower numbers of whitefly eggs, nymphs, and adults, in comparison to the rice straw mulch and bare ground treatments. Chili plants cv. Bara was more resistant than Bhaskara against B. tabaci in the field; however, in the no-choice trial, no significant difference was detected between both cultivars. Insecticide applications twice per week and once per week were equally effective in controlling the whitefly on the susceptible cultivar (Bhaskara). Overall, the integration of reflective mulch, resistant cultivar, and insecticide application every two weeks effectively suppressed B. tabaci populations on the chili pepper. This approach could substantially reduce the number of insecticide applications from twice per week (commonly practiced by chili farmers in the area) to one application only in two weeks.